Light sources technologies and applications - Kitsinelis, Spyridon (Taylor & Francis, 2015)
This book provides a description of modern light sources, covering their uses in a range of sciences and industries as well as the relevant scientific and engineering principles. The authors discuss incandescent and discharge sources along with more modern lasers and solid state light sources. They also explore various applications across a range of areas, from general lighting to specialized uses that require specific emissions, such as in sterilization, health science, medicine, food processing, and spectroscopy. The book is essential for those dealing with light sources and their applications in spectroscopy, optics, and industry